Smaller and thinner long bones in children and adolescents with cerebral palsy and other neuromotor impairments - Hodgson, Erin; Condliffe, Elizabeth G.; Gabel, Leigh (Frontiers in Endocrinology, 2025)
Introduction/BackgroundCompromised bone and muscle health is a significant concern for children and youth with cerebral palsy (CP) and other non-progressive neuromotor impairments. Weak bones increase the incidence of fragility fractures and predispose individuals to lifelong problems, such as osteoporosis. ObjectivesThis study quantified bone and muscle health in children and adolescents with CP and other neuromotor impairments across all five gross motor function classification system (GMFCS) levels.MethodsPeripheral quantitative computed tomography (pQCT) scans of both tibiae were acquired at the 3%, 38%, and 66% of tibia length in 22 children and adolescents (4–17 years old) diagnosed with CP and “CP-like” neurodevelopmental conditions causing motor impairment. Age-, sex-, and ethnicity-matched Z-scores were generated in reference to a normative typically developing population for total bone mineral content (BMC), trabecular and cortical bone mineral density (Tb.BMD, Ct.BMD), cortical BMC (Ct.BMC), cortical area (Ct.Ar), cortical thickness (Ct.Th), periosteal and endosteal circumference, cortical section modulus (Z), and muscle cross-sectional area (MCSA).ResultsTibial total BMC, Tb.BMD, Ct.BMC, Ct.Th, Ct.Ar, periosteal circumference, Z, and MCSA were significantly lower in children with CP and CP-like conditions compared to typically developing peers (median Z-scores ranged from -2.66 to -1.09; p = 0.019 to <0.001) and showed greater deficits in children and adolescents with lower levels of motor function than those with higher functional abilities (GMFCS I-II vs III-V; p = 0.042 to <0.001). Endosteal circumference was not different from zero (p = 0.756) but was smaller in children and adolescents with lower levels of motor function (p = 0.042). Ct.BMD did not differ compared to typically developing youth (p = 0.202) or between functional abilities (p = 0.168). ConclusionsResults reveal that bone and muscle size, total and cortical content, and trabecular density are impaired in children with CP and CP-like conditions; however, cortical mineralization is not impaired. Therefore, the heightened risk of fragility fractures in children and adolescents with CP and CP-like conditions is likely due to smaller and thinner bone structure. Future investigation into bone microarchitecture is warranted.